Electric field effect on dynamic analysis of smart porosity-dependent nanocomposite sandwich plate resting on silica aerogel foundation considering carbon nanotubes agglomeration. (November 2019) - Zamani, Mohammad Hossein; Heidari-Rarani, Mohammad; Ariaei, Alireza
In this study, the influence of carbon nanotubes agglomeration is investigated on the electroelastic dynamic behavior of a sandwich plate. The smart sandwich plate consists of functionally graded porous layer as the core and piezoelectric layers as the face sheets, which is subjected to the harmonic electrical loading. In order to take into account the continuum model for the silica aerogel foundation of the smart structure, the modified Vlasov's model is applied. The porosity distribution of the core layer varies non-uniformly throughout the thickness due to the non-uniform function. The equivalent material properties of nanocomposite core layer are determined using the Eshelby–Mori–Tanaka approach, in which the influence of carbon nanotube agglomeration is considered. For modeling the electroelastic fact sheets behavior, the piezoelasticity theory is adopted. On the basis of non-polynomial shear and normal deformation theory, the governing equations of motion are inferred applying the Hamilton's principle and the obtained equations are solved by an iterative procedure. The verification is accomplished through the available results in the literature and the influences of carbon nanotube agglomeration, different geometrical parameters, porosity index, and applied voltage are assessed on the dynamic deflection of nanocomposite sandwich plate.